The Lived Experiences of Students and Teachers with Disability in Keller’s and Wright’s Autobiographical Works - Budhathoki, Mahendra Kumar (Pursuits: A Journal of English Studies, 2023)
The study explores the lived experiences of students and teachers with disabilities inside schools/colleges while pursuing their studies and working in Hellen Keller’s The Story of My Life and Mary Herring Wright’s Sounds Like Home: Growing up Black and Deaf in the South. This study inquires what they have experienced and how they have made meanings from the campus phenomena. This research has utilized the disability studies theory, specially based on Alice Hall and Tobin Siebers, to interpret the selected autobiographical texts, and note-taking technique has been used to collect the required information from the autobiographical texts. The findings of the study are that the school/college infrastructures, practices, the executives’ attitudes are unfriendly, hostile and adverse to the students and teachers with disabilities while pursuing studies and working at schools/colleges. They suggest that the executives, administrators and other physically normal teachers and students can create the disabled-friendly physical, academic and social environment at the educational institutions if they slightly modify their attitudes and practices, and eliminate their conscious negligence to the needs of the disabled. The findings of the study can motivate the executives to enable physical and social (attitudes and practices) environment and service delivery, address the needs and demands of the disabled, and manage the required sources/materials and performance assessment system in schools/campuses.